The Effect of Profitability, Leverage, Corporate Social Responsibility and Executive Character on Tax Avoidance on Manufacturing Companies Listed on the Indonesia Stock Exchange Period 2016-2020 - Salna Djolafo (Economics, Business, Accounting & Society Review, 2022)
This study aims to analyze the effect of profitability, leverage, corporate social responsibility and executive characteristics on tax avoidance. The population in this study are all companies engaged in manufacturing which are listed on the Indonesia Stock Exchange from 2016-2020. The sample was selected using purposive sampling method with research criteria, in order to obtain as many as 38 companies. The data analysis technique used in this research is multiple linear regression analysis. The results of this study indicate that profitability and leverage affect tax avoidance, but for corporate social responsibility variables, executive character and company size as control variables do not affect tax aggressiveness while the F test results show that the variables of profitability, leverage, corporate social responsibility, executive character and firm size simultaneously affect the tax avoidance variable.